2020
DOI: 10.1088/1742-6596/1700/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Online learning readiness during the Covid-19 pandemic

Abstract: Online learning is one of the main alternatives to learning during the Covid-19 pandemic and the new normal period. This learning has been implemented at various levels of education with various platforms. Various studies have shown that online learning has varying effectiveness at all levels and types of education. The implementation of online learning is not supported by an in-depth study of student readiness. Student readiness in online learning can be assessed comprehensively from the aspects of equipment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 9 publications
3
25
0
4
Order By: Relevance
“…The comfortable level of students to study online during the COVID-19 pandemic can be related to student readiness. Widodo et al (2020) reported that student readiness in online learning depend on few aspects, such as: equipment capability, technology skills, motivation, and perceived usefulness on the benefits of online learning.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The comfortable level of students to study online during the COVID-19 pandemic can be related to student readiness. Widodo et al (2020) reported that student readiness in online learning depend on few aspects, such as: equipment capability, technology skills, motivation, and perceived usefulness on the benefits of online learning.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Faktor kesiapan mengajar bagi guru dan dan kesiapan belajar bagi mahasiswa dan para siswa ini tidak boleh diabaikan dalam media yang berbeda ini (Jalal, 2020). Berdasarkan pengertianpengertian berikut disimpulkan bahwa, kesiapan untuk pembelajaran online dinyatakan sebagai waktu manajemen, keterampilan membimbing diri, yang sifatnya dari pembelajaran online, mengadopsi sumber daya internal motivasi, pengenalan gaya belajar pribadi, dan pengalaman (Widodo et al, 2020) Konsep kesiapan pembelajaran online bermula dari sektor pendidikan dan pelatihan kejuruan di Australia oleh Warner dalam (Engin, 2017). Hung, 2010 dalam (Suwarsono et al, n.d.) (Hidayat, n.d.).…”
Section: Pendahuluanunclassified
“…The capability of the device is related to online learning readiness in terms of facilities, particularly computer equipment and internet access. Technology skills are related to the ability of students to access and use technology, particularly information and communication technology [3].…”
Section: Introductionmentioning
confidence: 99%